2017
DOI: 10.1038/srep46722
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically unpolarized single-photon source in diamond with intrinsic randomness

Abstract: Polarization is one of the fundamental properties of light, providing numerous applications in science and technology. While ‘dynamically unpolarized’ single-photon sources are demanded for various quantum applications, such sources have never been explored. Here we demonstrate dynamically unpolarized single-photon emission from a single [111]-oriented nitrogen- vacancy centre in diamond, in which the single-photon stream is unpolarized, exhibiting intrinsic randomness with vanishing polarization correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In this study, we used a commercially available sample produced by CVD (chemical vapor deposition), corresponding to Element Six's highest purity diamond (type IIa, 2 × 2 × 0.5 mm 3 ), whose nitrogen impurities are below 5 ppb (usually < 1 ppb) and the concentration of nitrogen vacancies are lower than 0.03 ppb. Crystallographic orientation is 100% single sector [100] and polishing. The diamond crystal lattice presents inversion symmetry, due to its cubic structure, and second-order nonlinearities are absent.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we used a commercially available sample produced by CVD (chemical vapor deposition), corresponding to Element Six's highest purity diamond (type IIa, 2 × 2 × 0.5 mm 3 ), whose nitrogen impurities are below 5 ppb (usually < 1 ppb) and the concentration of nitrogen vacancies are lower than 0.03 ppb. Crystallographic orientation is 100% single sector [100] and polishing. The diamond crystal lattice presents inversion symmetry, due to its cubic structure, and second-order nonlinearities are absent.…”
Section: Resultsmentioning
confidence: 99%
“…These experiments showed that the creation of the NV center is a stochastic process. (21,86) Besides, in Figure 53 we can see that the minimum time to create an ensemble of NV is 2 s, at the power level and conditions used here. From the zero-field ODMR, we observed that the local field (strain) around the NV center is much higher than usual, and it changes with the illumination time, this may be because the femtosecond laser modifies the local structure of the diamond, in the region illuminated by the laser.…”
Section: Third Experimentsmentioning
confidence: 92%
See 3 more Smart Citations